Education in the moral domain - Nucci, Larry P. (Cambridge University Press, 2001)
"Education in the Moral Domain brings together the results of twenty-five years of research on the domain theory of social cognitive development. On the basis of that research - which shows that morality is a domain distinct from other social values - the author provides concrete suggestions for creating a moral classroom climate, dealing with student discipline and integrating moral values within the curriculum." "Among questions addressed are the following: Is morality a set of rules we acquire like any other? Are there universal aspects to morality, or is it culture specific? Is there such a thing as moral character? How best can teachers make use of our knowledge about children's moral and social growth in their everyday classroom practices?" "Integrated answers to these questions result in a comprehensive approach that does not reduce moral education to a process of induction or inculcation, but rather harnesses children's intrinsic motivation to comprehend and master their social worlds."--Jacket